REVITALIZATION OF THE LAKE TOBA AREA: SWOT ANALYSIS IN THE ECONOMIC DEVELOPMENT OF THE NORTH SUMATRA REGIONAL - Feby Milanie; Azhar Paras Muda Hasibuan; Yustina Rizki Hasibuan; Yusen Effendy; Suhenpi Laia; Hendra Gunawan Halawa; Nasti Hasyim Nasution; Afrida Nursanti; Rita Efriyenni R (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The Lake Toba area has great potential as an attractive tourist destination and as the main driving force for regional economic growth in North Sumatra. SWOT analysis is used as the main basis for designing a revitalization strategy for this area. SO and ST strategies utilize internal strengths to optimize external opportunities and overcome threats. However, the relationship between WO and WT strategies presents complexity, where they complement each other despite potential contradictions. This understanding of SWOT provides a comprehensive view of the factors influencing regional economic development, enabling the formulation of integrated strategies. This strategy includes improving tourism infrastructure, developing local community skills, and integrated regulations. Support from the central government, international institutions and the private sector is essential in implementing this strategy. With this holistic approach, it is hoped that the revitalization of the Lake Toba area can make a significant contribution to economic growth and welfare of local communities, while ensuring the preservation of the environment and local culture.